Development of an electric vehicle charging management system using global navigation satellite system - Ng, Xian Wei (2014)
Since the world is changing towards clean renewable energy, electric vehicles (EVs) are seen as a new direction of clean energy. The reason is EVs are getting more efficient compared to internal combustion engine vehicles and more environment friendly as no carbon emissions. Moreover, it is increasingly treated as a maintainable mode of transport in Singapore and other countries. However, the limited availability of charging stations is a major hindrance to widespread adoption of EVs in Singapore and other countries due to EV drivers’ fear of running out of electric power. Thus, this project aims to have a charging management system (CMS) that uses Global Positioning System (GPS) to determine the exact positions of EVs, the locations of charging stations and distances and time taken to reach the destination. It also can calculate whether there is sufficient electric power for the vehicle to reach its desired destination. Moreover, the CMS uses a graphical user interface (GUI) on Windows platform that requires a GPS receiver to determine the EV location and CAN Bus Module for obtaining the SoC data from the EV battery. A formula is created to calculate the sufficiency of the EV battery to reach drivers' desired destination. This information allows the CMS to perform real-time charging predictions which provides EV drivers with navigation guide throughout the whole journey; and also navigation guide to the nearest charging stations when a charge is required. As a result, the fear of running out of electric power for EV users to reach their desired destination will be solved.